Hubungan Aktivitas Fisik Dengan Premenstrual Syndrome Pada Masa Pandemi Covid-19 - Eza Yusnella; Rize Budi Amalia; Nur Ainy Fardana Nawangsari (JURNAL KESEHATAN MERCUSUAR, 2022)
ABSTRACTPremenstrual syndrome (PMS) is a collection of symptoms or complaints by women on days 7-10 before menstruation until the end of menstruation. Symptoms include physical, psychological, and emotional which can affect lifestyle and behavior. The exact cause of PMS is still unknown, but it can be triggered and exacerbated by several factors, one of which is physical activity. The Covid-19 pandemic has an impact on the government's school from home policy to prevent transmission, indirectly changing physical activity, especially for female students which can exacerbate PMS symptoms experienced. This study aims to analyze the relationship between physical activity and PMS during the COVID-19 pandemic. The research method is observational analytic with cross sectional design. The study was conducted on female students of SMAN "A" Surabaya with an age 15-18 years. The number of samples 78 respondents with a sampling technique using proportional stratified random sampling. Bivariate analysis using Chi Square Test. The results showed that there were 46.2% moderate physical activity, with moderate PMS 57.7%. The results of statistical tests showed that there was a relationship between physical activity and PMS p = 0.001 (p < 0.05) with a Prevalence Ratio (PR) of 1.895 (95% CI 1.303-2.755). There is a significant relationship between physical activity and premenstrual syndrome in adolescent girls. Education and information on management efforts are urgently needed to reduce PMS complaints, especially during the COVID-19 pandemic.